(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Topic: Outcome analysis of 5 patients with recurrent antero-inferior shoulder dislocation and glenoid bone loss treated with open Latarjet procedure. Introduction: With the extreme range of movements, the shoulder joint is prone for dislocations. Selecting an optimal and efficient surgical procedure for patients with anterior glenohumeral instability and associated glenoid bone loss is a complex problem. Among the coracoid transfer procedures, open latarjet procedure offers good clinical outcomes even with glenoid bone loss. The purpose is to study the clinical outcome of Open Latarjet procedure in anterior glenohumeral instability using Carter Rowe scoring system. Aims & objectives: To evaluate the functional outcomes of 5 patinets with recurrent antero-inferior shoulder dislocation corrected by open Laterjet procedure using Carter Rowe Scoring system. Methodology: 5 patients with recurrent antero-inferior shoulder dislocation were operated by open latarjet procedure. All patients were screened clinically and confirmed on CT scan. Patients were followed up and reviewed at a mean time interval of 6 months and evaluated using Carter Rowe Score. Results: We have obtained complete bone union at 6 months in all patients with excellent to good results as scored by Carter Rowe scoring scale. In Range of motion, there was restriction in External Rotation. Patients were able to restore their daily activities by 6 months. No episode of dislocation, despite one epileptic patient having convulsed after 1 month of surgery. Conclusion: Open latarjet procedure offers a reliable surgical method of management of recurrent anterior shoulder dislocation with significant bone loss and our study showed good functional outcome as measured by Carter Rowe score.